Dual Face of Vγ9Vδ2-T Cells in Tumor Immunology: Anti- versus Pro-Tumoral Activities - Xiang, Zheng; Tu, Wenwei (Frontiers in Immunology, 2017)
Vγ9Vδ2-T cells are considered as potent effector cells for tumor immunotherapy through directly killing tumor cells and indirectly regulating other innate and adaptive immune cells to establish anti-tumoral immunity. The anti-tumoral activity of Vγ9Vδ2-T cells is governed by a complicated set of activating and inhibitory cell receptors. In addition, cytokine milieu in tumor microenvironment can also induce the pro-tumoral activities and functional plasticity of Vγ9Vδ2-T cells. Here, we review the anti- versus pro-tumoral activities of Vγ9Vδ2-T cells, and discuss the mechanisms underlying the recognition, activation, differentiation and regulation of Vγ9Vδ2-T cells in tumor immunosurveillance. The comprehensive understanding the dual face of Vγ9Vδ2-T cells in tumor immunology may improve the therapeutic efficacy and clinical outcomes of Vγ9Vδ2-T cell-based tumor immunotherapy.